2016
DOI: 10.1007/s00432-015-2109-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival advantage of lymphadenectomy in endometrial cancer

Abstract: Pelvic/para-aortic lymphadenectomy should be performed in all patients with endometrial cancer at intermediate and high risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Although two prospective randomized trials 10 and a Surveillance, Epidemiology and End Results (SEER) Program analysis 11 have reported that systematic lymphadenectomy did not improve overall or disease-free survival in EC, there are still several studies suggesting that lymphadenectomy is beneficial for EC. 12,13 Predictions of LNM are well studied in EC patients, especially in FIGO stage I. One recent study constructed a nomogram for predicting the overall survival and found the nomogram was more accurate than the Mayo criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although two prospective randomized trials 10 and a Surveillance, Epidemiology and End Results (SEER) Program analysis 11 have reported that systematic lymphadenectomy did not improve overall or disease-free survival in EC, there are still several studies suggesting that lymphadenectomy is beneficial for EC. 12,13 Predictions of LNM are well studied in EC patients, especially in FIGO stage I. One recent study constructed a nomogram for predicting the overall survival and found the nomogram was more accurate than the Mayo criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The recent debate focused on the value of routine lymphadenectomy in patients with EC comprises a three-fold controversy: first, randomized trials suggest the absence of survival benefit in patients undergoing systematic lymphadenectomy; second, potential post-operative morbidity following lymphadenectomy may jeopardize the patients' quality of life; and third, difficulty in procedural lymphadenectomy in obese patients is gradually increasing in a substantial proportion of the patient population (8081). Emerging evidence supports the survival benefit of systematic lymphadenectomy in select patients with EC at intermediate or high risk for nodal metastasis (8283). This highlights the importance of risk stratification in patients with indication of lymphadenectomy, to balance the therapeutic benefit against perioperative morbidity and mortality.…”
Section: Endometrial Carcinomamentioning
confidence: 93%
“…This highlights the importance of risk stratification in patients with indication of lymphadenectomy, to balance the therapeutic benefit against perioperative morbidity and mortality. However, in current clinical setting, optimal pre-operative risk assessment remains difficult (83).…”
Section: Endometrial Carcinomamentioning
confidence: 99%
“…The included studies were published between 2007 and 2016. Four studies were studies were conducted in Japan, [ 7 , 10 , 16 ] 3 in Korea, [ 15 , 17 ] 1 in Turkey, [ 12 ] 1 in Germany, [ 11 ] 1 in USA. [ 13 ] The average of follow-up duration was 46 months.…”
Section: Resultsmentioning
confidence: 99%